Sporting the government: Twitter as a window into sportspersons’ engagement with causes in India and USA - Mishra, Dibyendu; Sen, Ronojoy; Pal, Joyojeet (Broken Mirror 2021, 2021)
With the ubiquitous reach of social media, influencers are increasingly central to articulation of political agendas on a range of topics. We curate a sample of tweets from the 200 most followed sportspersons in India and the United States respectively since 2019, map their connections with politicians, and visualize their engagements with key topics online. We find significant differences between the ways in which Indian and US sportspersons engage with politics online – while leading Indian sportspersons tend to align closely with the ruling party and engage minimally in dissent, American sportspersons engage with a range of political issues and are willing to publicly criticize politicians or policy. Our findings suggest that the ownership and governmental control of sports impact public stances on issues that professional sportspersons are willing to engage in online. It might also be inferred, depending upon the government of the day, that the costs of speaking up against the state and the government in power have different socio-economic costs in the US and India.